The Use of Aripiprazole in Young Children with Autism Spectrum Disorders: The Treatment and 16 Week Follow-Up of a 23-Month-Old Male Patient - Percinel, Ipek; Yazici, Kemal Utku (Mary Ann Liebert, Inc, 2016)
[Abstract Not Available]
Keywords: Pediatric-Patients; Irritability; Adolescents; Antipsychotics; Behavior; Safety; Label